Alegoria e morte em Pedro Páramo, de Juan Rulfo: o futuro em ruínas - Cantarelli, Ana Paula (2013)
This paper proposes an analysis on the novel Pedro Páramo, by Juan Rulfo, in which elements such as the conception of future and past defended by Modernity, the allegorical construction and the work of mourning arise as central axis. Throughout four chapters we sought to answer the following question: How, in Pedro Páramo, the Mexican revolutionary process and future prospects arising from Modernity are expressed? In the first, based on authors like Carlos Fuentes, Alejo Carpentier, Jorge Alberto Vital and Ruffinelli, we linked the author, the work and the context of production in an attempt to apprehend the formation of the Mexican historical-social-economic reality. Also at this stage, we make some considerations about the processes of cultural encounters experienced by Mexico (since the arrival of the Spanish to the mexican revolution) in order to relate issues of modernity and the constitutive process of the novel studied. In the second chapter, we detailed the process of the narrative construction, associating the external to the internal elements in a process of entry and exit of the novel, adding the literary text to the Mexican political-historical-social context. Also, we used the concept of literary transculturation proposed by the Uruguayan critic Ángel Rama, who helped us understand the narrative structure of Rulfo s novel, especially in relation to the historical moment in which it was produced. In the third chapter, we approached the cultural elaboration of death in Mexico, in its condition as national totem. Furthermore, based on the studies developed by Walter Benjamin, Jürgen Habermas, Octavio Paz and Darcy Ribeiro, we related, to the narrative analyzed, Benjamin s concept of allegory and the temporal conception adopted in Modernity. In the fourth and final chapter, the writings of Theodor Adorno and Idelber Avelar helped us with concepts such as mourning, loss, defeat, tension - associated to negative dialectics - taking Pedro Páramo as an open system in which the tension leads to a conception of future that subverts the conception presented by Modernity: a future in ruins. The projection of a future in ruins turns active the past, the present and the future. In this light, the different narrative voices in Pedro Páramo are taken as different possibilities, singular and incomplete, which propose the revision of the constitution of the Great National Report of Mexico related to the Revolution, starting from the recognition of the past as heterogeneous and fragmented, breaking with the homogenizing and totalizing visions of history and taking diversity and opposition as positive aspects.